2018
DOI: 10.1155/2018/9184136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Passenger Flowlines at Zhongchuan High-Speed Railway Station

Abstract: In order to optimize the passenger flowlines and improve the operation capacity of Zhongchuan high-speed railway station, the simulation model of passenger flowlines is established based on the simulation software of Anylogic. e simulation of the passenger flowlines during peak and off-peak hours of the station are carried out respectively. e organization problems of passenger flowlines during peak hours are found out, and the optimization methods are put forward. e station capacity after optimization is compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The use of simulation models in metro stations has been widely studied in the literature. The simulation framework of an urban railway station escalator using the software Anylogic expanded the results of previous studies reported in [22,31,32].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The use of simulation models in metro stations has been widely studied in the literature. The simulation framework of an urban railway station escalator using the software Anylogic expanded the results of previous studies reported in [22,31,32].…”
mentioning
confidence: 87%
“…The study demonstrates the flexibility and effectiveness of using simulation models to understand and optimize pedestrian flow in metro stations. Another study by Wang et al [32], discusses the analysis and optimization of passenger flowlines at a high-speed railway station using Anylogic simulation software version 8.1. The simulation model of passenger flowlines was established to simulate passenger flow during peak and off-peak hours.…”
Section: Existing Studies On Escalators In Urban Railway Stationsmentioning
confidence: 99%
“…According to research, the critical value of passenger transfers is 15 minutes [35]. Considering the waiting time, 20 min is chosen here.…”
Section: Weighted Average Travel Time (Watt)mentioning
confidence: 99%
“…Hoy et al [14] examined passenger flow in Toronto's Union Station using future demand scenarios, indicating that unplanned increases in demand can significantly disrupt passenger flow and station operations. Wang et al [31] attempted an optimization of passenger flow lines at the Zhongchuan high-speed rail station in China, demonstrating that lengthening walk distances in the station can increase overall flow by reducing interference in the station. Cheung and Lam [5] looked at flow inside Hong Kong's Mass Transit Railway stations, focusing on pedestrian facilities such as stairways.…”
Section: Literature Reviewmentioning
confidence: 99%